Severe oral involvement in a case of Hand-Schuller-Christian disease - Kokelj, F... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
We report the case of a patient with diabetes insipidus who came to our observation because of severe lesions of the oral mucosa. He referred that he had lost all his molars and three incisors over the past two years. The clinical cutaneous examination revealed the presence of small yellowish-brown papules on the forehead only. A biopsy performed from the gingival mucosa showed the presence of Langherans cells and a dense inflammatory infiltrate. The immunohistochemical examination showed CD1 antigenic determinant and S-100protein positive. Considering the presence of diabetes insipidus, the clinical, histological, immunohistochemical picture, the diagnosis was of a Hand-Shuller-Christian disease. The patient underwent chemotherapy and radiotherapy. Three months after the end of the therapy a gingival biopsy confirmed the success of the treatment.
Keywords: Diabetes insipidus; Diagnosis; Hand-schueller-christian syndrome; Immunohistochemistry; Langerhans cells; Oral manifestations; Therapy; Treatment outcome